Where others fear to tread: the role of journalists in the creation and spreading of negative stereotypes about Roma people - Veselková, Zuzana (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2019)
This paper deals with the representation of ethnic minorities in the media, focusing mainly on the role of the journalist. It approaches news stories through the prism of the media construction of reality and the cultural concept of representation. Using critical discourse analysis, the study describes the nature of the social reality constructed by the TV news series “Where Others Fear to Tread.” The paper reflects the general attributes of the representation of the Roma minority in the news, pointing out methods and signs used for emphasizing the stereotypes shared by the majority. The analysis shows that the media discourse of news stories could potentially confirm prejudices towards the Roma minority, forming the image of Roma people as essentially maladjusted, dangerous and suspicious individuals.